THE SOCIAL NEEDS OF THE ELDERLY IN SOUTH BANGKA - Indriana, Yeniar; Al Karim, Chamilul Hikam; Arif Febriyanto; Dedy Yuni Hardi, (International Journal of Scientific Research and Management (IJSRM), 2021)
The social needs of the elderly in the South Bangka Regency were expressed through the needs of affiliation, succorance, and deference. These needs seem to dominate the behavior of the elderly out there. Social ties with neighbours are very strong and each of them avoids conflicts or disputes. This study aimed to see which social needs were the most dominant among these needs so that the local government could be more appropriate in developing the social welfare programs for the elderly in their regions. This research involved 311 elderly people from 8 (eight) sub-districts in South Bangka Regency. The sampling technique used proportional random sampling based on the area of ​​each district. The results showed that the need for succorance was the most dominant with a mean rank of 548.09, the need for affiliation hit second place with a mean rank of 541.72 and the last one was the need for deference with a mean rank of 311.20. This showed that the need for attention was more dominant than the need to build a relationship and conformity with others. There is no difference in social needs between men and women, nor is there a significant relationship with age.